2017
DOI: 10.1111/fcre.12303
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Residence for Children After Parental Separation: Recent Findings from Belgium

Abstract: In recent decades there have been two significant legislative amendments to shared parenting in Belgium. In 1995, joint exercise of parental responsibilities was introduced as the default legal position. In 2006, the legislation required that in all cases of joint parenthood in which parents could not agree on children's living arrangements, equally divided alternating residence must first be considered by the judge. In this article, we summarize recent research findings from Belgium about alternating residenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 17 publications
(22 reference statements)
3
39
0
3
Order By: Relevance
“…33 That evaluation also found that children in shared-time arrangements "fared marginally better" than children in maternal residence-except where mothers reported "safety concerns" (p. 273). This finding is consistent with studies of sharedtime parenting and children's outcomes in the United States (see also Poortman & Van Galaan, 2017;Vanassche et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…33 That evaluation also found that children in shared-time arrangements "fared marginally better" than children in maternal residence-except where mothers reported "safety concerns" (p. 273). This finding is consistent with studies of sharedtime parenting and children's outcomes in the United States (see also Poortman & Van Galaan, 2017;Vanassche et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in several Western countries, states, and regions, custody laws were revised in the last couple of years that underline the importance of ongoing co‐parental involvement (e.g., Australia : Smyth & Chisholm, ; Belgium : Vanassche, Sodermans, Declerck, & Matthijs, ; Catalonia, Spain : Solsona & Spijker, ; Italy : De Blasio & Vuri, ; Sweden : Singer, ; The Netherlands : Poortman & van Gaalen, ; UK : Nikolina, ; Wisconsin, USA : Meyer et al., ). Interestingly, none of the jurisdictions in those countries legislated with a 50/50 share in mind.…”
Section: Joint Physical Custody: Definition Legal Context and Prevamentioning
confidence: 99%
“…Also in other countries, the prevalence of joint physical custody arrangements in separated or divorced families has increased in the last couple of years. They make up to about 40% in Belgium (Vanassche et al., , p. 549) and Sweden (Bergström et al., ; p. 769), about 30% in Norway (Kitterød & Wiik, , p. 561), about 20% in Denmark (Spruijt & Duindam, , p. 66), 5% (Ontario) to 40% (Quebec) in Canada (Bala et al., , p. 520), 16% in Australia (Smyth & Chisholm, ; p. 594), 22% in the Netherlands (Poortman & van Gaalen, , p. 533), 15% in Spain—again with large variations between different regions (Solsona & Spijker, , p. 302), and 12% in the UK (Harris‐Short, , p. 258). Although JPC arrangements have increased during recent decades in all of these countries, it seems that they have now plateaued in some of them (e.g., Wisconsin, Australia, and the Netherlands).…”
Section: Joint Physical Custody: Definition Legal Context and Prevamentioning
confidence: 99%
“…However, it seems that in some countries it is much more widespread than in others. However, JPC families (symmetric and asymmetric) make up about 40% of all separated or divorced families in Belgium (Vanassche, Sodermans, Declerck, & Matthijs, 2017) and Sweden (Bergström et al, 2015), and these care arrangements are less prevalent in other countries like Australia (16%) (Smyth & Chisholm, 2017), or Spain (15%; Solsona & Spijker, 2016). After all, we have numbers only for countries where the phenomenon is known and thus gets some attention.…”
Section: Introductionmentioning
confidence: 99%